Finite frequency H∞ control for wind turbine systems in T-S form - Salma Aboulem; Abderrahim EL-Amrani; Ismail Boumhidi (Institute of Advanced Engineering and Science, 2020)
In this work, we study H∞ control wind turbine fuzzy model for finite frequency(FF) interval. Less conservative results are obtained by using Finsler’s lemma technique, generalized Kalman Yakubovich Popov (gKYP), linear matrix inequality (LMI) approach and added several separate parameters, these conditions are given in terms of LMI which can be efficiently solved numerically for the problem that such fuzzy systems are admissible with H∞ disturbance attenuation level. The FF H∞ performance approach allows the state feedback command in a specific interval, the simulation example is given to validate our results.